BS ISO 13266. Thermoplastics piping systems for non-pressure underground drainage and sewerage. Thermoplastics shafts or risers for inspection chambers and manholes. Determination of resistance against surface and traffic loading. (25th March 2020) - British Standards Institution,
No abstract available